Pengaruh Atraksi dan Amenitas Terhadap Kepuasan Pengunjung di Batu Kuda Manglayang - Andi Irzilya Fitri Desriana; Irena Novarlia; Dally Nur Arif (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Its natural, cool, and green environment, Batu Kuda Manglayang also attracts tourists with its long-standing legend. A tourist attraction is an attraction that has its own value so that it attracts tourists to come to a location. One of the main factors in tourism growth is the provision of tourist facilities. However, Batu Kuda Manglayang still faces a number of common problems related to facilities and infrastructure. Improving the quality of damaged or under-functioning facilities is one way to make visitors happy with the tourist attractions and services of Batu Kuda Manglayang. This study uses a quantitative methodology combined with a descriptive strategy. This study focuses on the quality of tourism (X) which is an independent variable consisting of two dimensions, namely facilities (X2) and attractions (X1). The variable of tourist satisfaction (Y) is the dependent variable. The indicators used to measure tourist satisfaction are the adequacy of expectations, interest in returning to visit, and the desire to recommend. Based on the results of the research that has been conducted, namely: Batu Kuda Manglayang provides camping, picnic, trekking, and cultural sites and other tourist attractions. Tourists can get satisfaction from the various attractions available. Thus, there is a fairly close relationship between the attraction variable and the tourist pleasure variable. 2) The variable of tourist amenities has a significant influence on tourist satisfaction, at least in part. This can increase tourist satisfaction if the facilities are sufficient and clean. 3) In Batu Kuda Manglayang, both attractions and tourist facilities have a significant influence on visitor satisfaction.